The Effect of Addition of AMF (Arbuscular Mycorrhizal Fungi) and Yomari Liquid Organic Fertilizer Concentration on the Growth of Agarwood Production Plants (Aquilaria malacensis Lamk.) on Ex-Lime Mining Soil - Satria, Benni; Martinsyah, Rachmad Hersi; Armansyah, Armansyah; Hervani, Dini; Warnita, dan (International Journal of Environment, Agriculture and Biotechnology, 2023)
This plant has a very large opportunity to be developed on ex-mining land, considering that this plant is an adaptive non-timber forest product plant that grows and produces naturally without inoculation (injection) on ex-mining land: limestone, nickel, rocky sand, tin and coal. and added witharbuscular mycorrhizal fungi (AMF) and liquid organic fertilizer such as Yomari on Aquilaria malacensis Lamk. AMF is able to increase root growth, root range, so that it can facilitate roots to absorb water and nutrients through external hyphae and later obtained quality seeds which have many and strong roots. Yomari liquid organic fertilizer has high organic and nutrient content, can increase soil organisms and improve soil pH and. This study aimed to obtain the best interaction between the dose of AMF and the concentration of Yomari liquid organic fertilizer on the growth of Aquilaria malacensis Lamk seedlings. in the ex-limestone mine soil, the best dose of AMF was obtained on the growth of Aquilaria malacensis Lamk seedlings. in limestone ex- mining soil and the best concentration of Yomari organic fertilizer on the growth of Aquilaria malacensis Lamk. in the former limestone quarry. This research was conducted from June to November 2022 in the nursery of the Faculty of Agriculture, Andalas University. This study used a factorial experimental method in a Completely Randomized Design (CRD) with 2 factors, namely the first factor was the administration of the AMF dose which consisted of 5 levels: 0.0 grams (C0); 15 grams (C2); 30 grams (C3) and 45 grams (C4) and the second factor concentration of Yomari organic fertilizer consisted of 5 levels: 0.00 ppm (Y0); 25.00 ppm (Y1); 50.00 (Y2); 75.00 ppm (Y3) and 100.00 ppm (Y4), each treatment level consisted of 4 replications. Observational data in the form of qualitative and quantitative data were analyzed using the F-test at a significance level of 5%. The different effects on the treatment were analyzed by further test of LSD at 5% level. Observations were made including: percentage of live seedlings, increase in seedling height, increase in number of leaves, widest leaf width, root weight, and percentage of roots infected by AMF on lime-mined soil media. There is an interaction between the dose of AMF and the concentration of liquid organic fertilizer on the growth of agarwood-producing plant seeds (Aquilaria malacensis Lamk.)) on the ex-limestone mining soil. Giving a dose of AMF 45 grams with a concentration of 100 ppm liquid organic fertilizer was the best in increasing the percentage of life, increasing the number leaves, increase in plant seed height, widest leaf width, percentage of agarwood-producing plant seeds infected with AMF.